An Observational Investigation of Behavioral Contagion in Common Marmosets (Callithrix jacchus): Indications for Contagious Scent-Marking - Massen, Jorg J. M.; Šlipogor, Vedrana; Gallup, Andrew C. (Frontiers in Psychology, 2016)
Behavioural contagion is suggested to promote group coordination that may facilitate activity transitions, increased vigilance and state matching. Apart from contagious yawning, however, very little attention has been given to this phenomenon, and studies on contagious yawning in primates have so far only focused on Old World monkeys and apes. Here we studied behavioural contagion in common marmosets, a species for which group coordination and vigilance are paramount. In particular, we investigated the contagiousness of yawning, stretching, scratching, tongue protrusion, gnawing and scent-marking. We coded these behaviours from 14 adult marmosets, from two different social groups. During testing sessions, animals were separated into groups of four individuals for 20-minute observation periods, across three distinct diurnal time points (morning, midday and afternoon) to test for circadian patterns. We observed almost no yawning (0.12 yawns / hour) and very little stretching behaviour. For all other behaviours, which were more common, we found several temporal and inter-individual differences (i.e., sex, age, dominance status) predictive of these responses. Moreover, we found that gnawing and scent-marking, that almost always co-occurred as a fixed-action pattern, were highly temporally clustered within observation sessions. We discuss the relative absence of yawning in marmosets as well as the possible function of contagious scent-marking, and provide suggestions for future research into the proximate and ultimate functions of these behaviours in marmosets.